A randomised placebo controlled 12 week trial of budesonide and prednisolone in rheumatoid arthritis. Issue 6 (12th May 2004) - Kirwan, J R; Hällgren, R; Mielants, H; Wollheim, F; Bjorck, E; Persson, T; Book, C; Bowman, S; Byron, M; Cox, N; Field, M; Kanerud, L; et al.
Abstract : Objectives: To compare budesonide, a locally acting glucocorticoid with minimal systemic exposure, with conventional glucocorticoid treatment and placebo in rheumatoid arthritis. Methods: A double blind, randomised, controlled trial over 12 weeks in 143 patients with active rheumatoid arthritis, comparing budesonide 3 mg daily, budesonide 9 mg daily, prednisolone 7.5 mg daily, and placebo. Particular attention was paid to the pattern of clinical response and to changes in the four week period following discontinuation of treatment. Results: There were improvements in tender joint count and swollen joint count on budesonide 9 mg compared with placebo (28% for tender and 34% for swollen joint counts, p<0.05). Prednisolone 7.5 mg gave similar results, while budesonide 3 mg was less effective. ACR20 response criteria were met by 25% of patients on placebo, 22% on budesonide 3 mg, 42% on budesonide 9 mg, and 56% on prednisolone 7.5 mg. A rapid and significant reduction in symptoms and signs in response to budesonide 9 mg and prednisolone 7.5 mg was evident by two weeks and maximal at eight weeks. There was no evidence that budesonide provided a different pattern of symptom control from prednisolone, or that symptoms became worse than placebo treatment levels after discontinuation of glucocorticoid treatment. Adverse effects attributable to glucocorticoids were equally common in all groups. Conclusions: The symptomatic benefits of budesonide 9 mg and prednisolone 7.5 mg are achieved within a short time of initiating treatment, are maintained for three months, and are not associated with any rebound in symptoms after stopping treatment.